The frequency of detection of markers of Сytomegalovirus infection in children with recurrent respiratory diseases in patients with Shiga-toxin-associated hemolytic-uremic syndrome (STEC-HUS) - I. B. Repina; L. V. Feklisova; M. K. Khadisova; N. V. Karazhas; E. I. Likhanskaya (Детские инфекции (Москва))
The paper presents data on the detection and role of cytomegalovirus infection (CMVI) in 146 children of certain groups aged from 3 months to 15 years who were hospitalized — frequently ill children with respiratory pathology, patients with shiga-toxin-associated hemolytic uremic syndrome (STEC-HUS) and schoolchildren with somatic diseases during rehabilitation in a sanatorium.The aim of the study was to determine the frequency of detection of CMVI in the presented groups, the originality of the main clinical manifestations in correlation with the markers of activity of herpesvirus type V infection. Clinical monitoring was carried out, oropharyngeal swabs, saliva,blood samples (serum and blood cells) were studied using a set of laboratory diagnostic methods:RCM (rapid culture method) on Vero- and M-19 cells, IIR (reaction of indirect immunofluorescence), ELISA to detect specific antigens and antibodies (IgM, IgG).The detection rate of CMV IgG in diagnostic values ranged from 6.4% in the group of frequently ill children with respiratory pathology to 31.7% in schoolchildren of the sanatorium, the acute course of infection was detected in3.2% and 6.4%, respectively, based on markers of acute infection (CMV IgM and cytomegalovirus antigen). In patients with STEC-HUS CMV IgG in diagnostic titers were recorded with the highest frequency — in 74.4% of patients.